Starch Deposition and Carbohydrase Activities in Developing and Germinating Soya Bean Seeds - Adams, C. A.; Rinne, R. W.; Fjerstad, M. C.
Immature soya bean seeds accumulate starch as a transient reserve material which is utilized later in development. Germinating seeds also accumulate starch reserves, probably as a result of gluconeogenesis from storage lipid. Developing beans show a rapid increase in y?-amylase activity which continues into early germination before declining. Distribution of /?-amylase activity is not consistent with its supposed role in starch degradation. Soya bean seeds also contain a-amylase and a-glucosidase activities which could be responsible for starch mobilization.
Keywords: GLYCINE MAX (L.)MERR.; SOYA BEAN; STARCH; CARBOHYDRASE; AMYLASE; A-GLUCOSIDASE.